Buathra laborator ... - Ghahari, Hassan (Zenodo, 2016)
Buathra laborator (Thunberg, 1824) Material examined: Province of Tehran, Pakdasht, 35°28′N 51°46′E, 1 ♀, 14-15.V.2013 . General distribution: Austria, Azerbaijan, Belgium, Bulgaria, Canada, China, Czech Republic, Finland, France, Germany, Greenland, Hungary, Iran, Italy, Japan, Kazakhstan, Korea, Kyrgyzstan, Latvia, Lithuania, Luxembourg, Moldova, Mongolia, Netherlands, Norway, Poland, Romania, Russia, Spain, Sweden, Switzerland, Tajikistan, Turkey, Turkmenistan, United Kingdom, USA, Uzbekistan. Host records: It has been reported from Malacosoma disstria H̡bner, 1820, M. neustria (Linnaeus, 1758) (Lepidoptera: Lasiocampidae), Melanolophia imitata (Walker, 1860) (Lepidoptera: Geometridae), Acronicta leporina (Linnaeus, 1758), Panolis flammea (Denis & Schifferm̡ller, 1775), Rhizedra lutosa (H̡bner, 1803) (Lepidoptera: Noctuidae), Promachus magnus Bellardi, 1861 (Diptera: Asilidae). ... : Published as part of Ghahari, Hassan, 2016, A study on the fauna of Ichneumonidae (Hymenoptera) in the province of Tehran, Iran., pp. 125-132 in Arquivos Entomolóxicos 16 on page 128, DOI: 10.5281/zenodo.12765681 ...